Use of Essential Oils to Inhibit Alicyclobacillus Acidoterrestris: A Short Overview of the Literature - Bevilacqua, Antonio (Frontiers in Microbiology, 2011)
Essential oils (EOs) are promising and friendly antimicrobials for the prolongation of the shelf life of many foods. They have been extensively used to inhibit spoiling and pathogenic microorganisms of many kinds of productslike fruit juices and acidic drinks. Therefore, they could be used successfully to control the germination of spores of Alicyclobacillus acidoterrestris, that finds in these products an optimal environment for growth. This paper reports a brief overview of the literature available, focusing on the effects of EOs towards alicyclobacilli.